Halal food culture in Kuala Terengganu: shariah perspective (Istitabat al-'Arab) - Syed Omar, Sharifah Sakinah Habibah; Abdul Karim, Mohd Hafiz; Jamaludin, Mohammad Aizat; Ahmad Fadzillah, Nurulhidayah (Faculty os Islamic Civilization Studies, KUIS, 2017)
Difference cultures posses particular uniqueness in their culinary styles. Members in a society connect with each other through similar food patterns. People from different cultural backgrounds consume different foods with different culinary styles including ingredients used, preparation methods and consumption habits. Variations in food culture are basically due to different situations faced which vary according to different societies. Religion is perceived to play a part in shaping Kuala Terengganu's food culture along with availability of food sources, geographical background, and historical background as well as migration. Considering that Kuala Terengganu is a predominantly Muslim district, its local food culture is by any means manifested by the prescription of Shariah law, which is to consume halalan tayyiban and to bypass haram. This study attempts to review the concept of Istitabat Al-'Arab pertaining to halal food rulings through various references found in different Quranic verses, hadith and principles. Also in this study, the different interpretation from major denominations in Islam (i.e. Hanafi, Maliki, Shafii and Hanbali) regarding the concept of Istitabat al-'Arab are discussed. Hence, this particular paper explains the concept Istitabat al-'Arab in Shariah perspective in shaping Kuala Terengganu's halal food culture with reference to local food rulings.